EFEKTIVITAS RADIO MEGASWARA DALAM MEMPERTAHANKAN EKSISTENSI DI ERA DIGITAL - Wida Hartika; M. Saddad Sulaiman; Hamdan Nurfalah; M. Hikmi Ukhrowi; Siti Rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digitalization has significantly transformed the media industry, including radio as a form of mass communication. This transformation requires radio stations to adapt in order to remain relevant and maintain their existence amid competition with digital media platforms. This study aims to analyze the effectiveness implemented by Radio Megaswara in responding to digitalization and sustaining its existence within society. The research employs a qualitative approach with a descriptive design, using data collection techniques such as observation, interviews, and documentation. The findings indicate that Radio Megaswara is relatively effective in maintaining its existence through the utilization of digital platforms such as online streaming and social media, strengthening the role of broadcasters as interactive communicators, and presenting content that is relevant to audience needs. Digitalization plays a crucial role in expanding audience reach and enhancing engagement. However, challenges remain, particularly in attracting younger audiences who tend to prefer digital-based media. Therefore, continuous innovation and adaptation are essential to sustain the effectiveness and existence of Radio Megaswara in the digital era